Tn and STn are members of a family of carbohydrate tumor antigens that possess carbohydrate–carbohydrate interactions. (3rd April 2018) - Sletmoen, Marit; Gerken, Thomas A; Stokke, Bjørn T; Burchell, Joy; Brewer, C Fred
Abstract: The mucin-type O -glycome in cancer aberrantly expresses the truncated glycans Tn (GalNAcα1-Ser/Thr) and STn (Neu5Acα2, 6GalNAcα1-Ser/Thr). However, the role of Tn and STn in cancer and other diseases is not well understood. Our recent discovery of the self-binding properties (carbohydrate–carbohydrate interactions, CCIs) of Tn (Tn–Tn) and STn (STn–STn) provides a model for their possible roles in cellular transformation. We also review evidence that Tn and STn are members of a larger family of glycan tumor antigens that possess CCIs, which may participate in oncogenesis.